Теоретичні аспекти розвитку фінансового потенціалу бурякоцукрового підкомплексу України в умовах євроінтеграції - Трусова, Наталя Вікторівна; Данилишин, Михайло Степанович; Trusova, Natalia; Danylyshyn, Mykhailo (Одеса : Видавничий дім «Гельветика», 2024)
UA: У статті розглянуто теоретичні аспекти розвитку фінансового потенціалу бурякоцукрового підкомплексу України в умовах євроінтеграції. Обґрунтовано, що переорієнтація бурякоцукрового підкомплексу Укра їни на європейський напрямок дозволяє адаптувати його фінансову складову до методів, важелів та інструментів фінансової системи, яка об’єднується в цілісну та підпорядковану структуру, забезпечуючи злагодженість усіх її елементів, що інтегруються із зовнішнього (європейського) до внутрішнього серед овища, формуючи системність функціональної компоненти окремої галузі за допомогою та під впливом факторів, що швидко змінюють платформу фінансового потенціалу на новий якісний рівень розвитку. Визначено основні підходи до розвитку фінансового потенціалу бурякоцукрового підкомплексу. В симбі озі категоріального апарату визначено нову дефініції «фінансовий потенціал бурякоцукрового підкомплексу». /// EN: The article examines the theoretical aspects of the development of the financial potential of the sugar beet sub-complex of Ukraine in the conditions of European integration. It is substantiated that the reorientation of the sugar beet sub-complex of Ukraine in the European direction allows to adapt its financial component to the methods, levers and tools of the financial system, which is combined into a coherent and subordinate structure, ensuring the coherence of all its elements, which are integrated from the external (European) to the internal environment , forming the system of the functional component of a separate industry with the help and under the influence of factors that quickly change the platform of financial potential to a new qualitative level of development. The main approaches to the development of the financial potential of the beet sugar sub-complex have been determined. In the symbiosis of the categorical apparatus, a new definition of "financial potential of the brown-sugar sub-complex" is presented. It has been proven that the financial potential of the sugar beet sub-complex is a complex multifaceted structure that embodies functional components and their elements that can be used to implement innovations, accumulate assets as reserves or stocks for future periods. This orientation of financial potential is a synthesis of the characteristics of features such as "asset", "reserve", "stock". It is substantiated that the integration of European institutions into the institutes for the development of the beet-sugar sub-complex surrounding the agricultural production branch and the sugar branch of the food industry, in the parameters of "consumers, competitors, suppliers, infrastructure, financial relations", allows to combine them into a single system and expand the functions "external market signals" of financial potential. External market signals are equated with financial indicators to determine the optimal criteria for the formation of added value and balance the stimulating factors and destimulating factors of "green" finance, which identify the real possibilities of financial resources for the requirements of European institutions.
Theoretical aspects of the development of the financial potential of the beet sugar sub-complex of Ukraine in the conditions of European integration
Keywords: фінансовий потенціал; фінансові інструменти; бурякоцукровий підкомплекс; джерела фінансування; «зелені»; фінанси; євроінтеграція; financial potential; financial instruments; beet sugar sub-complex; sources of financing; "green"; f inance; European integration